Using X-ray computed tomography to investigate mortar subjected to freeze-thaw cycles. (April 2020) - Sokhansefat, Ghazal; Moradian, Masoud; Finnell, Mark; Behravan, Amir; Ley, M. Tyler; Lucero, Catherine; Weiss, Jason
Abstract: This work uses X-ray computed micro tomography (XCT) to investigate the role of the critical degree of saturation (DOS) and air void system on the crack propagation of portland cement mortar subjected to freeze-thaw cycles. Three-dimensional imaging before and after freezing allow quantitative measurements on the location and volume of the formation of new cracks and the infilling of air voids. Cracks present before freeze-thaw cycles are observed to extend and new cracks initiate from the paste-aggregate interface. In addition, calcium-rich products were observed to fill >20% of the volume of the air voids with a diameter <50 μm. These observations provide insights into the freeze-thaw performance of mortar and are a step in understanding the damage in concrete.